The High Gain Rectangular Microstrip Patch Array Antenna for UHF-band Microsatellite Application - The Oo Lwin; Aung Myo Thu; Aung Ko Wynn (AI Society & STMIK Indonesia, 2026)
A UHF-band microsatellite receiving antenna requires high gain to support short-range communication between the ground station and satellite. This paper presents a microstrtip array antenna with a 2×1 rectangular patch element configuration using a microstrip line feeding technique. The array enhcances gain and directivity by employing a two-element planar design.Additionally, corner truncation on the patch and an 8mm thick substrate improve performance. The antenna is fabricated on Rogers RT 5880 dielectric material with a relative permittivity of 2.2 and a loss tangent of 0.0009. Copper is used for the patch and ground plane. The design is simulated and optimized using CST Microwave Studio. Simulation results show a return loss of -19.11dB and a VSWR of 1.2 at 410MHz. The antenna achieves a realized gain of 9.45 dB, indicating it is effective and sutibla for UHF-band microsatellite applications.